Linguistic and Cultural Study of Jaipur District : जयपुर जिले का भाषिक एवं सांस्कृतिक अध्ययन - Bunkar, Suman (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
Famous as the Paris of the East and the Pink City, Jaipur holds the honor of being the capital of Rajasthan. Renowned worldwide for its city planning, the quadrilateral-shaped Jaipur was constructed in accordance with the principles described in ancient architectural texts. This city, which preserves a unique historical and cultural heritage, stands as an exceptional example of modernity. Originally named Jaynagar after Maharaja Sawai Jai Singh II, the city of Jaipur was founded by him on 18th November, 1727 AD. The chief architect and city planner of this quadrilateral city was the renowned architect Vidhyadhar Acharya. The city was divided into nine blocks (chaukdis), and seven entrance gates were constructed around it. These include Chandpole Gate, Ajmeri Gate, Sanganeri Gate, Ghat Gate, Surajpole Gate, Gangapole Gate, and Zorawar Singh Gate, which still enhance the beauty of the city. All the buildings of Jaipur were painted pink by the then ruler Sawai Ram Singh II (1835–80) in 1876 AD to welcome Prince Albert to the city. Since then, Jaipur has been famously known as the Paris of India and the Pink City. After India gained independence, the princely states were unified, and Jaipur was honored with the status of the capital of Rajasthan. Abstract in Hindi Language: पूर्व का पेरिस तथा गुलाबी नगरी के नाम से प्रसिद्ध जयपुर को राजस्थान की राजधानी होने का गौरव प्राप्त है। अपने नगर नियोजन के लिए विश्वविख्यात चतुर्भुजाकार जयपुर की बनावट प्राचीन शिल्पशास्त्र में वर्णित सिद्धान्तों के अनुरूप है। अनोखी ऐतिहासिक एवं सांस्कृतिक धरोहर को अपने में संजोए यह शहर आधुनिकता का बेमिसाल नमूना है। महाराजा सवाई जयसिंह द्वितीय के नाम पर स्थापित जयनगर तत्पश्चात्् जयपुर की स्थापना उन्हीं के द्वारा 18 नवम्बर, 1727 ई. में की गई। नगर के प्रमुख वास्तुकार तथा नगर नियोजक प्रख्यात वास्तु-शिल्पी विद्याधर आचार्य थे, इस चतुर्भुजाकार नगर को नौ चैकड़ियों में विभाजित किया गया। नगर के चारों ओर सात प्रवेश द्वार बनाये गये। इनमें चांदपोल गेट, अजमेरी गेट, सांगानेरी गेट, घाटगेट, सूरजपोल गेट, गंगापोल गेट, जोरावर सिंह गेट आज भी शहर की शोभा बढ़ा रहे हैं। जयपुर नगर की सभी इमारतों को तत्कालीन जयपुर नरेश सवाई रामसिंह द्वितीय (1835-80) द्वारा 1876 ई. में प्रिंस अलबर्ट के जयपुर आगमन पर गुलाबी रंग से रंगवाया गया। तभी से जयपुर भारत का पेरिस व गुलाबी नगरी के नाम से विख्यात हो गया। स्वतंत्रता के बाद रियासतों का एकीकरण हुआ एवं जयपुर को राजस्थान की राजधनी बनने का गौरव प्राप्त हुआ।1 Keywords: वास्तुशिल्पी, ढूँढाड़, एकीकरण, भाषिक, सांस्कृतिक, बधावा, लहरिया।